Olfactory Loss in Parkinson's Disease - Antje Haehner; Thomas Hummel; Heinz Reichmann (Parkinson's Disease)
Impairment of olfaction is a characteristic and early feature of Parkinson's disease. Recent data indicate that >95% of patients with Parkinson's disease present with significant olfactory loss. Deficits in the sense of smell may precede clinical motor symptoms by years and can be used to assess the risk for developing Parkinson's disease in otherwise asymptomatic individuals. This paper summarizes the available information about olfactory function in Parkinson's disease, indicating the advantageous use of olfactory probes in early and differential diagnosis.